Penyutradaraan Naskah "Sepotong Riwayat Mamak" Karya Arga Purnama - Kurnia, Wahyu Kurnia; Aldys Salwa Zaleani; Amelia Ningsih (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This study examines the directorial process of "Sepotong Riwayat Mamak" (A Fragment of Mother's Story) by Arga Purnama, a drama addressing elderly abandonment in nursing homes. Using descriptive qualitative methods, the research explores technical and artistic challenges in adapting the script to realist theater performance. Findings reveal that thorough script analysis, accurate observation of elderly characters, and precise handling of performative elements including blocking, dialogue intonation, and background music are critical success factors. The study provides insights into the complexities of directing realist theater while highlighting the importance of empathy in portraying marginalized communities' lives. Challenges in actor preparation and symbolic element execution offer practical lessons for theater practitioners.